Cytoplasmic expression of AXL is associated with high risk of postoperative relapse of conventional renal cell carcinoma - Peterfi, Lehel; Bjercke, Thea; Yusenko, Maria V.; Kovacs, Gyula; Banyai, Daniel (Anticancer research, 2020)
Background/Aim: Despite early detection by widespread use of abdominal imaging more than 40% of patients with conventional renal cell carcinoma (RCC) will die due to metastatic disease. Small kinase inhibitors for AXL receptor tyrosine kinase may delay the progression of metastatic cRCC. Patients and Methods: We analysed AXL expression by immunohistochemistry on tissue multi arrays of 691 conventional RCC without metastasis at the time of nephrectomy. Results: The Kaplan-Meier survival analysis indicated a poor disease-specific survival rates for patients with tumour showing cytoplasmic AXL staining, whereas expression on the cell membrane is associated with excellent disease outcome. Multivariate Cox regression analysis identified cytoplasmic AXL expression as an independent prognostic factor indicating a five-times higher risk of postoperative tumour progression (RR=5.048; 95% CI=2.391-10.657; p<0.001). Conclusion: Detecting cytoplasmic expression of AXL can be used to define a subset of conventional RCC with high risk of progression, thus identifying patients for more aggressive surveillance and adjuvant AXL inhibitor treatment as early as possible.